2015
DOI: 10.1007/s12687-015-0255-z
|View full text |Cite
|
Sign up to set email alerts
|

Components of genetic counsellor education: A systematic review of the peer-reviewed literature

Abstract: The need for appropriately trained genetic counsellors to support genetic healthcare is now acknowledged. However, while programmes for education of genetic counsellors exist in a number of countries, these do not conform to any specific international standards. As genetic techniques, educational standards and professional standards have been evolved, and with increasing mobility of genetic counsellors, it is of great importance to have some comparison of education and training between different countries. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
(96 reference statements)
0
12
0
Order By: Relevance
“…6,9,13,19 The theoretical components of existing genetic counsellor's educational programmes are quite similar between countries, however the clinical components of the educational courses are less well addressed. 20 This might explain the seemingly diverse roles and wide spectrum of autonomy of genetic counsellors, as reported in this study.…”
Section: Discussionmentioning
confidence: 64%
“…6,9,13,19 The theoretical components of existing genetic counsellor's educational programmes are quite similar between countries, however the clinical components of the educational courses are less well addressed. 20 This might explain the seemingly diverse roles and wide spectrum of autonomy of genetic counsellors, as reported in this study.…”
Section: Discussionmentioning
confidence: 64%
“…For the current analysis, any peer-reviewed English language systematic or scoping review that synthesized empirical studies was included if it was published in January 2010 or later and if it included variables related to communication about CGT. Articles were excluded from the study when they were determined to be commentaries [28], narrative reviews without a systematic search process [29], contained less than two empirical studies focused on cancer-related genetic testing [30], were unrelated to clinical communication about CGT [31,32], or focused exclusively on family communication about CGT [33]. Figure 1 contains the full PRISMA 2009 flow chart for this review.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…12 means that there are huge differences in clinical experience in novice genetic counselors, even after accessing specialized training programs. 21 Particularly encouraging for a multidisciplinary team approach was the overwhelming consensus that the majority of tasks explored could be performed by either genetic counselors or medical geneticists. This shows that most genetic counselors can provide appropriate support, and are willing to take on responsibilities from team members, in order to achieve the team goals.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a study by Skirton et al, to determine the core curriculum for Master programs in genetic counseling, participating experts concluded that in addition to essential topics to be covered, 50% of the educational programs should be comprised of clinical practice . Taking into account the various duration and forms of clinical practice among existing programs, (ie, 28 weeks clinical rotations in France; approximately 10 weeks clinical rotation in Cuba; no clinical rotation in Norway) means that there are huge differences in clinical experience in novice genetic counselors, even after accessing specialized training programs …”
Section: Discussionmentioning
confidence: 99%